Расчет пограничного слоя на лопатке газовой турбины с использованием модифицированной модели турбулентности Себеси-Смитта - Иванченко, Е. Н. (НТУ "ХПИ", 2009)
The results of numerical investigations of a turbulent boundary layer of a gas turbine blade and comparison with the experimental data are presented. Calculated investigation are executed using the modification of the Cebeci-Smith turbulence models. Numerical results and experimental data are in good agreement
Keywords: теплообмен; коэффициенты теплоотдачи; конфигурации решеток; турбулентный пограничный слой